Inkjet textile printing ink set and image formation method

By using the ink collection containing hydrolyzable cationic urea compounds in pigment inkjet ink, the problems of uneven image density, insufficient friction durability and damage to fabric material are solved, and better image quality and ink stability are achieved.

JP2025040660APending Publication Date: 2025-03-25KONICA MINOLTA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023147588
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Prior art When using pigment inkjet ink, the image density formed on the fabric is uneven, the friction durability is insufficient, and the storage and injection stability is poor, and the texture of the fabric may be damaged.

Method used

The ink collection containing a hydrolyzable cationic urea compound is used, which includes a block copolymer containing two hydrolyzable ends as the pigment dispersant, and a hydrolyzable anionic urea resin as the binder.

Benefits of technology

Improves uniformity of image density and friction durability while maintaining the texture of the fabric and improving the storage and jet stability of ink.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040660000001
    Figure 2025040660000001
  • Figure 2025040660000002
    Figure 2025040660000002
  • Figure 2025040660000003
    Figure 2025040660000003
Patent Text Reader

Abstract

To provide an ink set for inkjet textile printing that enables formation of an image with excellent uniformity of image density and friction resistance without impairing texture.SOLUTION: An ink set for inkjet textile printing comprises: an ink for inkjet textile printing, including a pigment, a pigment dispersant, a water-dispersible anionic urethane resin, and an aqueous solvent; and a treatment liquid containing a water-soluble cationic urethane compound. The pigment dispersant of the ink for inkjet textile printing includes a block copolymer comprising: two hydrophilic blocks A that are located at both molecular ends and interact with the pigment; and a hydrophobic block B disposed between the two hydrophilic blocks A.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ink set for ink-jet textile printing and an image forming method. [Background technology]

[0002] In recent years, ink-jet printing, in which an image is formed on a fabric by an ink-jet system, has become popular as a textile printing method because it allows dyeing in a short time and has high production efficiency.

[0003] Dye inks have been the mainstream inks used in inkjet textile printing, but the use of pigment inks, which can omit post-treatment such as a washing step for washing away dye that has not dissolved or reacted, is being considered.

[0004] In pigment inks, the pigment is usually dispersed using a pigment dispersant to facilitate dispersion of the pigment. The use of block copolymers and the like as pigment dispersants has been considered.

[0005] In addition, while pigment inks exhibit high color development by retaining pigment particles on the surface of the fabric, they tend to have poorer fixation of pigment particles and inferior friction resistance compared to dye inks. Therefore, studies are being conducted to improve the fixation of pigment particles and increase image density and friction resistance by adding binder resin (resin particles) to the ink or applying a treatment liquid onto the ink.

[0006] For example, Patent Document 1 discloses an aqueous inkjet ink containing a pigment, a pigment dispersant, an acrylic resin emulsion or a urethane resin as a binder resin, water, and a water-soluble organic solvent. As the pigment dispersant, a triblock copolymer consisting of a hydrophobic polymer block (polymer chain A) and two types of hydrophilic polymer blocks (polymer chains B and C) is used. This document states that the ink can improve color development and fixation when an image is formed on plain paper.

[0007] Patent Document 2 discloses an ink composition containing a pigment, a pigment dispersant, a urethane resin as a binder resin, a nonionic surfactant, water, and a water-soluble organic solvent. A diblock copolymer consisting of a hydrophilic block and a hydrophobic block is used as the pigment dispersant. This document states that the ink can improve the ejection stability.

[0008] In addition, as an ink set for inkjet printing, for example, Patent Document 3 discloses an ink set including an overcoat liquid including a water-dispersible resin, a specific water-soluble organic solvent, a crosslinking component, and water. In the examples, an anionic urethane resin is used as the water-dispersible resin. In this document, it is said that the anionic urethane resin reacts with the crosslinking component to form a strong film on the ink coating, thereby improving the abrasion fastness. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2019-210389 A [Patent Document 2] International Publication No. 2015 / 152290 [Patent Document 3] JP 2017-149812 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, when the inks disclosed in the above-mentioned Patent Documents 1 and 2 are used to form an image on a fabric, not only does the fabric become hard and lose its texture, but the image density and resistance to friction are not sufficient. Furthermore, the ink storage stability and ejection stability are also insufficient.

[0011] Furthermore, in the ink set disclosed in Patent Document 3, the binder component contained in the overcoat liquid is prone to forming a resin film when heated, which causes the fabric to become hard and the texture to be easily damaged.

[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide an ink set for ink-jet textile printing and an image forming method that are capable of forming an image having good uniformity in image density and good resistance to friction without impairing the texture. [Means for solving the problem]

[0013] The above problem can be solved by the following configuration.

[0014] [1] An inkjet textile printing ink set comprising: an inkjet textile printing ink comprising a pigment, a pigment dispersant, a water-dispersible anionic urethane resin, and an aqueous solvent, wherein the pigment dispersant comprises a block copolymer including two hydrophilic blocks A that are arranged at both ends of a molecule and interact with the pigment, and a hydrophobic block B that is arranged between the two hydrophilic blocks A; and a treatment liquid that contains a water-soluble cationic urethane compound. [2] The ink set for ink-jet textile printing according to [1], wherein the hydrophilic block A contains a structural unit derived from a hydrophilic monomer which is a vinyl-based monomer containing a hydrophilic functional group selected from the group consisting of a hydroxyl group, a carboxyl group, and a sulfonic acid group, and a content of the structural unit derived from the hydrophilic monomer in the hydrophilic block A is higher than that in the hydrophobic block B. [3] The ink set for ink-jet printing according to [2], wherein the hydrophobic block B contains a structural unit derived from a hydrophobic monomer selected from the group consisting of vinyl monomers containing an aromatic ring group or an alicyclic hydrocarbon group, and the content of the structural unit derived from the hydrophilic monomer in the hydrophobic block B is lower than that in the hydrophilic block A. [4] A method for forming an image on a fabric using the inkjet textile printing ink set according to any one of [1] to [3], the image forming method comprising: applying the inkjet textile printing ink onto the fabric by an inkjet system; and applying a treatment liquid onto the fabric. Effect of the Invention

[0015] According to the present invention, it is possible to provide a textile printing ink set and an image forming method capable of forming an image having good uniformity of image density and good resistance to friction without impairing texture. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present inventors have discovered that by combining an ink containing a specific block copolymer with a treatment liquid containing a water-soluble cationic urethane compound, it is possible to improve the friction fastness and image density while maintaining a good texture.

[0017] The reason for this is not clear, but is presumed to be as follows. Conventional diblock copolymers have only one hydrophilic block, so a long hydrophilic block is required to obtain dispersion stability in the solvent. This makes it easy for the hydrophilic groups to entangle with each other in the solvent, and the micelle size of the pigment dispersion is likely to increase. This makes the size of the aggregates formed by the interaction between the pigment dispersion in the ink and the resin in the treatment liquid large, and the image density is likely to decrease. In addition, the large size of the aggregates reduces the contact area with the fabric, and the friction fastness is likely to decrease. In addition, since the diblock copolymer has one hydrophilic block, it is likely to bond continuously (in a film-like shape) at one bonding point with a fabric having a hydrophilic group (e.g., a hydroxyl group) or a fabric to which a cationic substance is attached. Furthermore, if the resin in the treatment liquid is a water-dispersible resin, a resin film is likely to be formed. For these reasons, the fabric becomes hard and the texture is likely to be damaged.

[0018] In contrast, in the present invention, a block copolymer having hydrophilic blocks at two locations on both ends of the molecule and a hydrophobic block between them is used as the pigment dispersant. This allows the length of the hydrophilic block to be shortened, reducing entanglement between hydrophilic groups and reducing the micelle size of the pigment dispersion. This also reduces the size of aggregates formed by the interaction between the pigment dispersion in the ink and the resin in the treatment liquid, allowing for improved image density and abrasion resistance. In addition, since the block copolymer has two hydrophilic blocks, the pigment dispersion and the fabric are bonded to two locations, and the bond distance is short, making it easy to bond in a dot pattern. In addition, the water-soluble urethane compound in the treatment liquid does not form a resin film. For these reasons, the fabric is less likely to become hard, and the texture can be well maintained. Therefore, the ink set of the present invention can improve the abrasion fastness and image density while maintaining the texture of the fabric in a good condition.

[0019] Furthermore, the present inventors have found that the use of the above ink makes it possible to improve ejection stability and storage stability.

[0020] That is, in inks using diblock polymers, hydrophilic groups are likely to be entangled in the solvent, which reduces the dispersibility of the dispersion in the ink and reduces the interaction between the pigment dispersion and the binder resin. In addition, because the ink has a long hydrophilic block, the dispersant is likely to be detached from the pigment due to shear during ink circulation, causing the pigment to aggregate, leading to filter clogging and reducing circulation and ejection properties. In contrast, when a specific block copolymer is used, the length of the hydrophilic block can be shortened, which reduces entanglement between hydrophilic groups and enhances the dispersibility of the dispersion in the ink, thereby improving the ink storage stability and ejection stability.

[0021] An ink set according to an embodiment of the present invention will be specifically described below.

[0022] 1. Inkjet textile printing ink set An ink set according to an embodiment of the present invention includes an ink-jet textile printing ink and a treatment liquid.

[0023] 1-1. Inkjet textile printing ink The inkjet textile printing ink (hereinafter also simply referred to as "ink") in this embodiment contains a pigment, a predetermined block copolymer as a pigment dispersant, a water-dispersible anionic urethane resin, and an aqueous solvent.

[0024] 1-1-1.Pigments The pigment contained in the ink is not particularly limited, but is preferably an organic pigment or an inorganic pigment having the following numbers as described in the Color Index.

[0025] Examples of orange pigments include Pigment Orange 31 and 43.

[0026] Examples of red or magenta pigments include Pigment Red 3, 5, 19, 22, 31, 38, 43, 48:1, 48:2, 48:3, 48:4, 48:5, 49:1, 53:1, 57:1, 57:2, 58:4, 63:1, 81, 81:1, 81:2, 81:3, 81:4, 88, 104, 108, 112, 122, 123, 144, 146, 149, 166, 168, 169, 170, 177, 178, 179, 184, 185, 208, 216, 226, 257, Pigment Violet 3, 19, 23, 29, 30, 37, 50, 88, Pigment Orange 13, 16, 20, 36.

[0027] Examples of blue or cyan pigments include Pigment Blue 1, 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, 17-1, 22, 27, 28, 29, 36, 60.

[0028] Examples of green or yellow pigments include Pigment Green 7, 26, 36, and 50. Examples of yellow pigments include Pigment Yellow 1, 3, 12, 13, 14, 15, 17, 34, 35, 37, 55, 74, 81, 83, 93, 94, 95, 97, 108, 109, 110, 128, 137, 138, 139, 151, 153, 154, 155, 157, 166, 167, 168, 180, 185, 193, and 213.

[0029] Examples of black pigments include Pigment Black 7, 28, and 26.

[0030] Commercially available examples of pigments include: Chromofine Yellow 2080, 5900, 5930, AF-1300, 2700L, Chromofine Orange 3700L, 6730, Chromofine Scarlet 6750, Chromofine Magenta 6880, 6886, 6891N, 6790, 6887, Chromofine Violet RE, Chromofine Red 6820, 6830, Chromofine Blue HS-3, 5187, 5108, 5197, 5085N, SR-5020, 5026, 5050, 4920, 4927, 4937, 4824, 4933GN-EP, 4940, 4973, 5205, 5208, 5214, 5221, 5000P, CHROMO FINE GREEN 2GN, 2GO, 2G-550D, 5310, 5370, 6830, CHROMO FINE BLACK A-1103, SEIKA FAST YELLOW 10GH, A-3, 2035, 2054, 2200, 2270, 2300, 2400(B), 2500, 2600, ZAY-260, 2700(B), 2770, SE Squid Fast Red 8040, C405(F), CA120, LR-116, 1531B, 8060R, 1547, ZAW-262, 1537B, GY, 4R-4016, 3820, 3891, ZA-215, Seika Fast Carmine 6B1476T-7, 1483LT, 3840, 3870, Seika Fast Bordeaux 10B-430, Seika Light Rose R40, Seika Light Violet B800, 7805, Seika Fast Maroon 460N, Seika Fast Orange 900, 2900, Seika Light Blue C718, A612, Cyanine Blue 4933M, 4933GN-EP, 4940, 4973 (Dainichi Seika Chemicals); KET Yellow 401, 402, 403, 404, 405, 406, 416, 424, KET Orange 501, KET Red 301, 302, 303, 304, 305, 306, 307, 308, 309, 310, 336, 337, 338, 346, KET Blue 101, 102, 103, 104, 105, 106, 111, 118, 124, KET Green 201 (manufactured by Dainippon Ink & Chemicals);Colortex Yellow 301, 314, 315, 316, P-624, 314, U10GN, U3GN, UNN, UA-414, U263, Finecol Yellow T-13, T-05, Pigment Yellow1705, Colortex Orange 202, Colortex Red101, 103, 115, 116, D3B, P-625, 102, H-1024, 105C, UFN, UCN, UBN, U3BN, URN, UGN, UG276, U456, U457, 105C, USN, Colortex Maroon601, Colortex BrownB610N, Colortex Violet600, Pigment Red 122, Colortex Blue516, 517, 518, 519, A818, P-908, 510, Colortex Green 402, 403, Colortex Black 702, U905 (Sanyo Pigment); Lionol Yellow 1405G, Lionol Blue FG7330, FG7350, FG7400G, FG7405G, ES, ESP-S (Toyo Ink Co., Ltd.); Toner Magenta E02, Permanent Rubin F6B, Toner Yellow HG, Permanent Yellow GG-02, Hostapearm Blue B2G (Hoechst Industry); Novoperm P-HG, Hostaperm Pink E, Hostaperm Blue B2G (manufactured by Clariant); Carbon black #2600, #2400, #2350, #2200, #1000, #990, #980, #970, #960, #950, #850, MCF88, #750, #650, MA600, MA7, MA8, MA11, MA100, MA100R, MA77, #52, #50, #47, #45, #45L, #40, #33, #32, #30, #25, #20, #10, #5, #44, CF9 (manufactured by Mitsubishi Chemical).

[0031] From the viewpoint of improving dispersibility in the ink, the pigment is preferably further dispersed with a pigment dispersant, which will be described later.

[0032] The pigment content is not particularly limited, but from the viewpoint of easily adjusting the viscosity of the ink to the range described below and forming a higher density image, it is preferably 0.3 to 12% by mass relative to the ink. If the pigment content is 0.3% by mass or more, the color of the obtained image tends to be vivid, and if it is 5% by mass or less, the viscosity of the ink does not become too high, so that the ejection stability is not easily impaired. From the same viewpoint, it is more preferable that the pigment content is 0.5 to 8% by mass relative to the ink.

[0033] 1-1-2. Pigment dispersants As described above, the pigment dispersant contains a block copolymer including two hydrophilic blocks A located at both ends of the molecule and a hydrophobic block B located therebetween.

[0034] The "hydrophilic block A" is a portion that enhances the affinity for aqueous solvents and has lower or no adsorptivity to pigment particles than the hydrophobic block B. The hydrophilic block A refers to a block that has a higher affinity for water among the blocks constituting the copolymer. The number of hydrophilic blocks is preferably two.

[0035] The hydrophilic block A contains a structural unit derived from a monomer having a hydrophilic functional group (hereinafter referred to as "hydrophilic monomer"). Examples of the hydrophilic functional group include a hydroxyl group, a carboxyl group, and a sulfonic acid group.

[0036] Examples of the hydrophilic monomer constituting the hydrophilic block A include vinyl monomers containing a hydrophilic functional group, and examples thereof include monomers containing a carboxyl group or an acid anhydride group, such as unsaturated polycarboxylic acids such as (meth)acrylic acid and maleic acid, and maleic anhydride, monomers containing a sulfonic acid group, such as styrenesulfonic acid and 4-(methacryloyloxy)butylsulfonic acid, and ethylene oxide-modified (meth)acrylic acid ester monomers, such as ethylene oxide-modified (meth)acrylic acid alkyl esters. Of these, the hydrophilic monomer is preferably (meth)acrylic acid, from the viewpoint of imparting appropriate water solubility to the hydrophilic block A.

[0037] The content of the constitutional units derived from hydrophilic monomers in the hydrophilic block A may be greater than the content of the constitutional units derived from hydrophilic monomers in the hydrophobic block B. Specifically, the content of the constitutional units derived from hydrophilic monomers in the hydrophilic block A is preferably 5% by mass or more relative to 100% by mass of the hydrophilic block A. When the content of the constitutional units derived from hydrophilic monomers is 5% by mass or more, not only is the dispersibility in aqueous solvents more likely to be improved, but the copolymer also more likely to interact or react with the flocculant, making it easier to improve the adhesion to the fabric. From the same viewpoint, the content is more preferably 10 to 40% by mass.

[0038] The hydrophilic block A may further contain a structural unit derived from a monomer other than the hydrophilic monomer. Examples of the other monomer include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate and tert-butyl (meth)acrylate. Among these, C2 or higher alkyl esters such as butyl (meth)acrylate are preferred. This is because the Tg of the block copolymer is low and the fabric is less likely to become hard. However, the other monomers do not include hydrophobic monomers described later.

[0039] The "hydrophobic block B" is a portion that is adsorbed to the pigment, and is a block that has a smaller affinity for the aqueous solvent contained in the ink among the blocks that constitute the copolymer. The number of hydrophobic blocks B is preferably one.

[0040] The hydrophobic block B contains a structural unit derived from a monomer having a hydrophobic functional group (hereinafter referred to as a "hydrophobic monomer"). Examples of the monomer having a hydrophobic functional group include vinyl monomers having an aromatic ring group or an alicyclic hydrocarbon group.

[0041] Examples of vinyl monomers having an aromatic ring group include (meth)acrylates having an aromatic ring group, such as benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate; and aromatic vinyl monomers such as styrene, α-methylstyrene, 4-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methoxystyrene, 2-hydroxymethylstyrene, and 1-vinylnaphthalene, among which vinyl monomers having an aromatic ring group having 6 to 15 carbon atoms are preferred.

[0042] Examples of vinyl monomers having an alicyclic alkyl group include (meth)acrylates having an alicyclic alkyl group such as cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate, and vinyl monomers having an alicyclic alkyl group having 6 to 15 carbon atoms are preferred.

[0043] Of these, from the viewpoint of improving the adsorption to the pigment, the hydrophobic monomer is preferably a vinyl monomer having an aromatic ring group having 6 to 15 carbon atoms, such as styrene.

[0044] The content of the structural units derived from hydrophobic monomers in the hydrophobic block B is preferably 80% by mass or more relative to the hydrophobic block B. When the content is 80% by mass or more, the adsorption to the pigment is more likely to be enhanced. From the same viewpoint, the content is more preferably more than 90% by mass, and further preferably 95% by mass or more.

[0045] The hydrophobic block B may further contain a structural unit derived from a monomer other than the hydrophobic monomer. Examples of the other monomer include the above-mentioned other monomers and the above-mentioned hydrophilic monomers. However, when the hydrophobic block B contains a structural unit derived from a hydrophilic monomer, the content ratio of the structural unit derived from the hydrophilic monomer in the hydrophobic block B is lower than that in the hydrophilic block A. Specifically, the content of the structural unit derived from the hydrophilic monomer is preferably 20% by mass or less, more preferably less than 10% by mass, and even more preferably 5% by mass or less, relative to the hydrophobic block B. In other words, of the two hydrophilic blocks A and B, the hydrophobic block B has the lowest content of the structural unit derived from the hydrophilic monomer (molar number of hydrophilic functional groups).

[0046] The content of the hydrophobic block B in the ABA block copolymer is preferably 20% by mass or more and 80% by mass or less, and more preferably 20% by mass or more and 50% by mass or less, based on the total mass of the block copolymer. When the content is 20% by mass or more, the content of the hydrophilic block A is small (or the molecular weight is small), so that crosslinking aggregation is more easily suppressed, and when the content is 80% by mass or less, the content of the hydrophilic block A is large (or the molecular weight is large), so that affinity to aqueous solvents is more easily increased.

[0047] When the hydrophilic block is A and the hydrophobic block is B, examples of the structure of the block copolymer include ABA type, ABABA type, etc. Among them, the block copolymer is preferably an ABA type block copolymer consisting of two hydrophilic blocks A arranged at both ends of the molecule and a hydrophobic block B arranged between them.

[0048] The types and compositional ratios of monomers in the multiple blocks A contained in the block copolymer may be the same as or different from each other. When the block copolymer contains multiple blocks B, the types and compositional ratios of monomers in the multiple blocks B may be the same as or different from each other. In particular, it is preferable that the two hydrophilic blocks A have the same monomer composition.

[0049] The weight average molecular weight of the block copolymer is preferably 5000 to 70000, and more preferably 7000 to 30000. The larger the weight average molecular weight, the easier it is to increase the dispersibility of the pigment in an aqueous solvent, and the smaller the weight average molecular weight, the easier it is to suppress crosslinking and aggregation between pigment dispersions. The weight average molecular weight of the block copolymer can be measured in polystyrene equivalent terms by gel permeation chromatography.

[0050] The molecular weight distribution (PDI) (weight average molecular weight (Mw) of the block copolymer) / (number average molecular weight (Mn) of the block copolymer) is preferably 2.0 or less, more preferably 1.8 or less. The lower the PDI, the narrower and more uniform the molecular weight distribution is, and therefore the better the dispersibility is.

[0051] The acid value of the block copolymer is, for example, preferably 40 to 400 mgKOH / g, more preferably 40 to 300 mgKOH / g, and even more preferably 40 to 190 mgKOH / g. When the acid value is 40 mgKOH / g or more, the hydrophilicity of the pigment dispersant is increased, and the dispersibility of the pigment can be further improved. When the acid value is 400 mgKOH / g or less, the hydrophilicity of the pigment dispersant is further prevented from being excessively increased, and the water resistance of the resulting image-formed product can be further improved. The acid value can be measured according to the measurement method of JIS K0070:1992.

[0052] The content of the block copolymer is preferably 10 to 50% by mass, more preferably 20 to 40% by mass, based on the pigment. When the content is 10% by mass or more, the dispersibility of the pigment in the pigment dispersion can be further improved. When the content of the pigment dispersant is 50% by mass or less, an increase in the viscosity of the pigment dispersion caused by an excessive amount of the pigment dispersant can be further suppressed.

[0053] The method for synthesizing the block copolymer is not particularly limited, but for example, the block copolymer can be obtained by sequentially polymerizing vinyl monomers constituting the blocks by a living radical polymerization method.

[0054] 1-1-3. Water-dispersible anionic urethane resin The water-dispersible anionic urethane resin (hereinafter, simply referred to as "anionic urethane resin") can function as a binder resin for fixing pigments and the like. Furthermore, the anionic urethane resin can have good affinity with the water-soluble cationic urethane compound in the treatment liquid. Therefore, the fixation of the aggregate formed by the pigment dispersion in the ink and the water-soluble cationic urethane compound in the treatment liquid to the fabric can be improved, and the image density and friction fastness can be further improved.

[0055] The anionic urethane resin can be present as resin particles dispersed in an aqueous medium. The anionic urethane resin may be a self-emulsifying type resin particle having a hydrophilic group introduced therein, or may be a forced emulsifying type resin particle that becomes water-dispersible by using an external emulsifier. From the viewpoint of suppressing bleed-out, the self-emulsifying type is preferred.

[0056] From the viewpoint of easier maintenance of the texture of the fabric, the glass transition temperature (Tg) of the anionic urethane resin is preferably low, and is preferably −70 to 50° C., more preferably −50 to 30° C., and even more preferably −50 to 0° C. The Tg of the resin can be measured at a temperature rise rate of 10° C. / min in accordance with JIS K7121.

[0057] The anionic urethane resin is a urethane resin having an anionic group. Examples of the anionic group include a carboxyl group, a sulfonic acid group, and a phosphonic acid group. The urethane resin having an anionic group may be any of a polyether type urethane resin, a polyester type urethane resin, and a polycarbonate type urethane resin. In addition, the urethane resin having an anionic group is preferably a self-emulsifying type. The self-emulsifying type urethane resin may be, for example, a polyaddition reaction product between a polyhydric alcohol having an anionic group and a polyvalent isocyanate.

[0058] Examples of commercially available products of the above anionic urethane resins include Takelac(R) W-6010 (polycarbonate type / anionic type), Takelac(R) W-6020 (ether type / anionic type), Takelac(R) W-6061 (ether type / anionic type), Takelac(R) W-6110 (carbonate type / anionic type), Takelac(R) W-405 (ester type / anionic type), Takelac(R) W-605 (ester type / anionic type), Takelac(R) WS-5000 (polyester type / anionic type), Takelac(R) WS-4000 (polycarbonate type / anionic type), Takelac(R) W-4000 (polyester type / anionic type), Takelac(R) W-4000 (polycarbonate ... Examples of the anionic urethane resin include SUPERFLEX(R) 126 (ether / ester, anionic type), SUPERFLEX(R) 130 (ether, anionic type), SUPERFLEX(R) 150 (ether / ester, anionic type), SUPERFLEX(R) 300 (ether / ester, weak anionic type), SUPERFLEX(R) 420 (polycarbonate / anionic type), and SUPERFLEX(R) 460 (polycarbonate / anionic type) (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.). The anionic urethane resin may be one type or two or more types.

[0059] The average particle size of the anionic urethane resin may be, for example, 20 to 300 nm, and preferably 30 to 200 nm. The average particle size of the anionic binder resin can be measured in the same manner as the average particle size of the pigment particles.

[0060] The content of the anionic urethane resin in the ink is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, based on the ink. When the content of the anionic urethane resin is equal to or greater than the lower limit, the fixability of the ink to the fabric is further improved. When the content of the anionic urethane resin is equal to or less than the upper limit, the fabric does not become too hard, and the texture of the fabric is further prevented from being damaged.

[0061] 1-1-4. Water-based solvents The ink is an aqueous ink containing an aqueous solvent, which preferably contains water and further contains a water-soluble organic solvent.

[0062] The content of water in the ink is, for example, preferably from 20 to 70% by mass, more preferably from 30 to 60% by mass, and even more preferably from 40 to 60% by mass.

[0063] The water-soluble organic solvent is not particularly limited as long as it is compatible with water, but from the viewpoint of making it easier for the ink to penetrate into the interior of the fabric and making it difficult for the ink ejection stability to be impaired in the inkjet method, it is preferable that the ink does not easily thicken due to drying. Therefore, it is preferable that the ink contains a high-boiling point solvent having a boiling point of 200° C. or more.

[0064] The high-boiling solvent having a boiling point of 200° C. or higher may be any water-soluble organic solvent having a boiling point of 200° C. or higher, and is preferably a polyol or a polyalkylene oxide.

[0065] Examples of polyols having a boiling point of 200°C or higher include dihydric alcohols such as 1,3-butanediol (boiling point 208°C), 1,6-hexanediol (boiling point 223°C), and polypropylene glycol; and trihydric or higher alcohols such as glycerin (boiling point 290°C) and trimethylolpropane (boiling point 295°C).

[0066] Examples of polyalkylene oxides having a boiling point of 200° C. or higher include ethers of dihydric alcohols such as diethylene glycol monoethyl ether (boiling point 202° C.), triethylene glycol monomethyl ether (boiling point 245° C.), tetraethylene glycol monomethyl ether (boiling point 305° C.), tripropylene glycol monoethyl ether (boiling point 256° C.) and polypropylene glycol, and ethers of trihydric or higher alcohols such as glycerin (boiling point 290° C.) and hexanetriol.

[0067] The solvent may further include other solvents in addition to the high boiling point solvent. Examples of the other solvents include polyhydric alcohols having a boiling point of less than 200° C. (e.g., ethylene glycol, propylene glycol, hexanetriol, etc.); polyhydric alcohol ethers having a boiling point of less than 200° C. (e.g., ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether); monohydric alcohols (e.g., methanol, ethanol, propanol, pentanol, hexanol, cyclohexanol, butyl ether ... alcohol); amines (e.g., ethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenediamine, triethylenetetramine); amides (e.g., formamide, N,N-dimethylformamide, N,N-dimethylacetamide); heterocycles (e.g., 2-pyrrolidone, N-methyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidine), sulfoxides (e.g., dimethyl sulfoxide); and sulfones (e.g., sulfolane).

[0068] The content of the water-soluble organic solvent in the ink is, for example, preferably 20 to 70% by mass, and more preferably 30 to 60% by mass.

[0069] 1-1-5.Other ingredients The ink may further contain other components in addition to those described above, if necessary. Examples of the other components include additives such as neutralizing agents, surfactants, preservatives, antifungal agents, and pH adjusters.

[0070] In this embodiment, when the block copolymer has an anionic group such as a carboxyl group or a sulfonic acid group, the ink may further contain a neutralizing agent. The neutralizing agent may be a known basic compound, such as sodium hydroxide, potassium hydroxide, ammonia, or triethylamine. When the pigment dispersion contains a neutralizing agent, the anionic group is appropriately promoted to dissociate in the pigment dispersion, and dispersibility can be further improved.

[0071] The content of the neutralizing agent is not particularly limited, but it is preferable that the neutralization rate is 30% or more and 100% or less. The neutralization rate can be calculated by the following formula (1).

[0072] Neutralization rate (%) = (mass of basic compound [g] / (equivalent of basic compound [g / mol] × valence of basic compound)) ÷ ((acid value of pigment dispersant [mgKOH / g] × mass of pigment dispersant [g]) / (56 [g / mol] × 1000)) (1)

[0073] The surfactant can reduce the surface tension of the ink and increase the wettability of the ink to the fabric. The type of the surfactant is not particularly limited, and can be, for example, an acetylene glycol surfactant, a silicone surfactant, a fluorine surfactant, or the like.

[0074] Examples of preservatives or antifungal agents include aromatic halogen compounds (eg, Preventol CMK), methylene dithiocyanate, halogen-containing nitrogen-sulfur compounds, 1,2-benzisothiazolin-3-one (eg, PROXEL GXL), and the like.

[0075] Examples of pH adjusters include citric acid, sodium citrate, hydrochloric acid, sodium hydroxide, and the like.

[0076] 1-2. Processing solution The treatment liquid in this embodiment contains a water-soluble cationic urethane compound and water.

[0077] 1-2-1. Water-soluble cationic urethane compounds The water-soluble cationic urethane compound interacts with the hydrophilic portion of the pigment dispersant or the water-dispersible anionic urethane resin contained in the ink, and can have the function of aggregating or fixing the pigment to the fabric. Unlike the water-dispersible cationic urethane compound, the water-soluble cationic urethane compound makes the fabric less likely to become hard, and can prevent the texture from being impaired.

[0078] The water-soluble cationic urethane compound contains a constitutional unit derived from polyethylene glycol and a tertiary amino group. The water-soluble cationic urethane compound does not form particles in an aqueous solvent at 25°C. Whether particles are formed can be determined, for example, by particle size distribution measurement. For example, if the distribution is not measured (not detected), it can be determined that particles are not formed. Such a water-soluble cationic urethane compound (hereinafter also referred to as "cationic urethane compound") can be obtained, for example, by reacting polyisocyanate (A), polyol (B) containing polyethylene glycol, and chain extender (C) containing a tertiary amino group, and then quaternizing at least a part of the tertiary amino group with an acid or the like.

[0079] That is, the cationic urethane compound contains a constituent unit derived from a polyisocyanate (A), a constituent unit derived from a polyol (B), and a constituent unit derived from a chain extender (C) containing a tertiary amino group; the constituent unit derived from the polyol (B) contains a constituent unit derived from a polyethylene glycol.

[0080] (Polyisocyanate (A)) The polyisocyanate (A) may be any one of an aliphatic polyisocyanate, an alicyclic polyisocyanate, and an aromatic polyisocyanate. The polyisocyanate (A) may be used alone or in combination of two or more kinds.

[0081] Examples of aliphatic polyisocyanates include tetramethylene diisocyanate, dodecamethylene diisocyanate, 1,4-butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, 3-methylpentane-1,5-diisocyanate, and the like.

[0082] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-cyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, and the like.

[0083] Examples of aromatic polyisocyanates include tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, α,α,α,α-tetramethylxylylene diisocyanate, and the like.

[0084] Among these, alicyclic polyisocyanates and aromatic polyisocyanates are preferred, and isophorone diisocyanate and tolylene diisocyanate are more preferred.

[0085] (Polyol (B)) The polyol (B) includes polyethylene glycol.

[0086] The number average molecular weight of the polyethylene glycol is not particularly limited, but is preferably 200 to 2000, and more preferably 200 to 1000. When the number average molecular weight of the polyethylene glycol is 200 or more, the molecule has a more flexible structure, and the texture can be further improved. On the other hand, when the number average molecular weight of the polyethylene glycol is 2000 or less, the solubility in aqueous solvents is less likely to be impaired, and the viscosity of the treatment liquid can be further reduced. The number average molecular weight of the polyethylene glycol can be measured in terms of polystyrene by gel permeation chromatography.

[0087] The polyol (B) may further contain other polyols than polyethylene glycol, as long as the water solubility is not impaired. Examples of other polyols include polyalkylene glycols other than polyethylene glycol, polyester polyols, etc.

[0088] Other examples of polyalkylene glycols include polypropylene glycol, polyethylene-polypropylene glycol, and the like. Examples of polyester polyols include those obtained by condensation reaction of polycarboxylic acid with polyol, preferably those obtained by reaction of dicarboxylic acid with aliphatic diol. Examples of dicarboxylic acid include malonic acid, citric acid, succinic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, terephthalic acid, and phthalic acid. Examples of aliphatic diols include 1,4-butanediol, 1,6-hexanediol, and diethylene glycol.

[0089] The content ratio of the polyethylene glycol-derived structural unit in the structural unit derived from polyol (B) is preferably 60% by mass or more, more preferably 80% by mass or more, based on the structural unit derived from polyol (B). When the content ratio of polyethylene glycol is 60% by mass or more, the solubility of the resulting compound in aqueous solvents is more easily increased, and the texture is also more easily improved. The upper limit of the content ratio is not particularly limited, but may be 100% by mass.

[0090] (Chain extender (C)) The chain extender (C) having a tertiary amino group is used to introduce a tertiary amino group for cationicization into the cationic urethane compound. Examples of the chain extender (C) having a tertiary amino group include N-alkyl dialkanolamines such as N-methyldiethanolamine and N-ethyldiethanolamine, N-alkyl diamino alkylamines such as N-methyldiaminoethylamine and N-ethyldiaminoethylamine, and triethanolamine. These chain extenders (C) having a tertiary amino group may be used alone or in combination of two or more.

[0091] At least a portion of the tertiary amino groups is preferably neutralized with an acid or quaternized with a quaternizing agent, thereby increasing the water solubility of the cationic urethane compound.

[0092] When the tertiary amino group is neutralized with an acid, the acid that can be used may be an organic acid such as formic acid, acetic acid, propionic acid, butyric acid, lactic acid, malic acid, malonic acid, or adipic acid, or an inorganic acid such as hydrochloric acid, phosphoric acid, or nitric acid.

[0093] When the tertiary amino group is quaternized with a quaternizing agent, examples of the quaternizing agent that can be used include alkyl halides such as benzyl chloride and methyl chloride, and sulfates such as dimethyl sulfate and diethyl sulfate.

[0094] The content of each structural unit may be adjusted so that the total moles of hydroxyl groups in the polyol (B) and the chain extender (C) / the moles of isocyanate groups in the polyisocyanate (A) is about 1.

[0095] Among these, the content of the structural unit derived from the chain extender (C) is preferably 5 to 15% by mass relative to the total of the structural unit derived from the polyisocyanate (A), the structural unit derived from the polyol (B), and the structural unit derived from the chain extender (C). When the content of the structural unit derived from the chain extender (C) is 5% by weight or more, the number of tertiary amino groups introduced increases and the cationicity also increases, so that not only the solubility in aqueous solvents increases, but also the effect of increasing the slipperiness of the fabric and the image layer is more easily obtained. On the other hand, if there are too many tertiary amino groups, water solubility may be impaired, so the content of the structural unit derived from the chain extender (C) is preferably 15% by mass or less.

[0096] The weight average molecular weight of the water-soluble cationic urethane compound is not particularly limited, but is preferably, for example, 600 to 10,000. When the weight average molecular weight of the cationic urethane compound is 10,000 or less, the solubility in an aqueous solvent can be more easily increased, and the viscosity of the treatment liquid can be further reduced. When the weight average molecular weight of the cationic urethane compound is 600 or more, the effect of imparting flexibility can be more easily obtained, and the texture can be more easily improved. From the same viewpoint, the weight average molecular weight of the cationic urethane compound is more preferably 600 to 3,000. The weight average molecular weight of the cationic urethane compound can be measured in terms of polystyrene by gel permeation chromatography.

[0097] The content of the cationic compound is preferably 1 to 10% by mass relative to the treatment liquid. When the content is 1% by mass or more, the texture is more easily improved. When the content is 10% by mass or less, the viscosity of the treatment liquid is more easily reduced, and the ejection stability is more easily improved. In addition, deterioration of the texture due to stickiness is less likely to occur. From the same viewpoint, the content is more preferably 2 to 6% by mass.

[0098] 1-2-2.Other ingredients The treatment liquid may further contain other components as necessary. Examples of the other components include water-soluble organic solvents, surfactants, preservatives, etc. These may be the same as the water-soluble organic solvents, surfactants, and preservatives used in the ink.

[0099] 2. Image forming method An image forming method according to one embodiment of the present invention includes the steps of 1) applying ink onto a fabric by an inkjet method, and 2) applying a treatment liquid onto the ink applied to the fabric. In this embodiment, an example will be described in which the ink and treatment liquid of the ink set described above are used as the ink and post-treatment liquid.

[0100] 2-1. Ink application process The ink is applied onto the fabric by an inkjet method.

[0101] The fibers constituting the fabric are not particularly limited, and include natural fibers such as cotton (cellulose fiber), hemp, wool, and silk; chemical fibers such as rayon, vinylon, nylon, acrylic, polyurethane, polyester, and acetate, and blended fibers thereof. Among these, the fibers constituting the fabric may be hydrophilic fibers such as cotton, hydrophobic fibers such as polyester, or blended fibers thereof. The fabric may be any form of these fibers, such as woven fabric, nonwoven fabric, knitted fabric, etc. The fabric may be a blended woven fabric or blended nonwoven fabric of two or more types of fibers.

[0102] The fabric may have an aggregating agent attached thereto for aggregating the pigment in the ink, etc. In other words, a treated fabric containing the fabric and the aggregating agent attached thereto may be used, which makes it easier to aggregate the pigment in the ink and the anionic urethane resin on the fabric.

[0103] The ink applied to the fabric may then be further dried.

[0104] The ink is dried by removing the solvent and the like contained in each liquid applied to the fabric. The drying method is not particularly limited, and the ink may be dried at room temperature or by heating. The heating method may be a method using a heater, a hot air dryer, a heating roller, or the like, and is preferably a method of heating the fabric from both sides using a hot air dryer and a heater.

[0105] The drying temperature is not particularly limited, but since the ink and the first treatment liquid contain a relatively large amount of polyhydric alcohols, it may be, for example, 80 to 180° C. In addition, the drying time may be, for example, 1 to 10 minutes, depending on the drying temperature.

[0106] 2-2. Post-processing process Next, the above-mentioned treatment liquid is applied as a post-treatment liquid onto the ink applied to the fabric, whereby the cationic compound adheres to cover the pigment on the fabric, thereby improving the fixation of the pigment and increasing the slipperiness of the surface.

[0107] The method for applying the treatment liquid is not particularly limited, and may be any of a dipping method, a spray method, and an ink-jet method, but is preferably the ink-jet method.

[0108] The amount of the treatment liquid applied is preferably 0.3 to 3.0 g / m 2 , more preferably 0.3 to 1.0 g / m 2 When the amount of the cationic urethane compound attached is within the above range, the texture of the fabric can be further improved.

[0109] The ink-jet composition applied to the fabric may then be dried. The drying method and conditions for the ink-jet composition may be the same as those for the ink.

[0110] 2-3. Other processes The image forming method according to the present embodiment may further include other steps as necessary. For example, a step of pretreating the fabric may be further carried out before the above step 2-1.

[0111] In the pretreatment step, for example, the fabric is brought into contact with a pretreatment liquid containing a flocculant, and then dried to obtain a fabric to which the flocculant is attached.

[0112] (Pretreatment solution) The pretreatment liquid contains a flocculant and an aqueous solvent.

[0113] The type of flocculant may be any that flocculates the pigments contained in the ink, and may utilize a change in pH or an electrical effect.

[0114] Examples of flocculants that cause flocculation by changing the pH include organic acids, such as carboxylic acids having 6 or less carbon atoms, saturated fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, and hexanoic acid, and hydroxy acids such as lactic acid, malic acid, and citric acid.

[0115] The flocculant that causes aggregation by electrical action includes a polyvalent metal salt, and a compound having a cationic group or an anionic group. For example, when the pigment dispersant contained in the ink is anionic, the flocculant preferably includes a polyvalent metal salt or a compound having a cationic group.

[0116] Polyvalent metal salts can be water-soluble compounds having a divalent or higher polyvalent metal ion and an anion associated with it. Examples of polyvalent metal ions include Ca 2+ , Cu 2+ , Ni 2+ , Mg 2+ , Zn 2+ , B.A. 2+ Divalent metal ions such as Al 3+ , Fe 3+ , Cr 3+ Examples of anions include trivalent metal ions such as Cl. - , I - , Br - , SO4 2- , ClO3 - , NO3 - , and H.C.O.O. - , CH3COO- Among these, calcium salts and magnesium salts are preferred, and calcium nitrate and calcium chloride are more preferred.

[0117] The cationic group in the compound having a cationic group includes a secondary amino group, a tertiary amino group, a quaternary ammonium base, etc. Examples of the compound having a cationic group include the above-mentioned cationic urethane compound. In addition, cationic resins such as cationic urethane resin, cationic olefin resin, and cationic allylamine resin may be used.

[0118] The aqueous solvent may be the same as the solvent for the ink-jet composition.

[0119] If necessary, the pretreatment liquid may further contain a pH adjuster, a preservative, etc. As the pH adjuster and the preservative, the same ones as those described above can be used.

[0120] The method for contacting with the pretreatment liquid may be the same as the method described above.

[0121] The amount of the coagulant applied is not particularly limited, but may be, for example, 0.1 to 5.0 g / m 2 It is possible.

[0122] In the above embodiment, the treatment liquid is used as a post-treatment liquid, but the present invention is not limited to this, and the treatment liquid may be used as a pre-treatment liquid. That is, the order of steps 1) and 2) is not limited, and the order of steps 2) and 1) may be used. EXAMPLES

[0123] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.

[0124] 1. Ink Preparation 1-1. Preparation of block copolymers <Preparation of Block Copolymer P-1> In a flask equipped with an argon gas inlet tube and a stirring blade, 138.8 g of n-butyl methacrylate (hereinafter referred to as "BMA"), 73.5 g of methyl methacrylate (hereinafter referred to as "MMA"), 59.6 g of methacrylic acid (hereinafter referred to as "MAA"), 23.3 g of ethyl-2-methyl-2-n-butyltellanyl-propionate (hereinafter referred to as "BTEE"), 14.3 g of dibutyl ditelluride (hereinafter referred to as "DBDT"), 2.6 g of 2,2'-azobisisobutyronitrile (hereinafter referred to as "AIBN"), 166.1 g of methyl ethyl ketone, and 166.1 g of acetonitrile were charged and reacted at 60°C for 18 hours. As a result, a prepolymer (hydrophilic block A1, Mw: 6920) was obtained.

[0125] A mixed solution of 233 g of benzyl methacrylate (hereinafter referred to as "BzMA"), 23.3 g of MAA, 2.6 g of AIBN, 98.0 g of methyl ethyl ketone, and 98.0 g of acetonitrile, which had been previously argon-substituted, was added to the above reaction solution, and the mixture was reacted at 60° C. for 9 hours. As a result, a prepolymer (Mw: 9910) containing a hydrophilic block A and a hydrophobic block B was obtained.

[0126] A mixed solution of 138.8 g of BMA, 73.5 g of MMA, 59.6 g of MAA, 1.3 g of AIBN, 61.1 g of methyl ethyl ketone, and 388.5 g of acetonitrile, which had been previously purged with argon, was added to the above reaction solution, and the mixture was reacted at 60° C. for 23 hours. As a result, a polymer (Mw: 13,800) containing hydrophilic block A1, hydrophobic block B, and hydrophilic block A2 was obtained.

[0127] After the reaction was completed, 3.6 kg of methyl ethyl ketone was added to the reaction solution, which was then poured into 21 L of heptane under stirring. The precipitated polymer was filtered by suction and dried to obtain a block copolymer P-1.

[0128] <Preparation of Block Copolymer P-2> A flask equipped with an argon gas inlet tube and a stirring blade was charged with 4.16 g of BMA, 2.20 g of MMA, 1.79 g of MAA, 0.70 g of BTEE, 0.43 g of DBDT, 0.08 g of AIBN, 6.20 g of methyl ethyl ketone, and 6.28 g of acetonitrile, and reacted at 60° C. for 13 hours. As a result, a prepolymer (hydrophilic block A1, Mw: 5790) was obtained.

[0129] A mixed solution of 7.00 g of cyclohexyl methacrylate (hereinafter referred to as "CHMA"), 0.70 g of MAA, 0.8 g of AIBN, 2.94 g of methyl ethyl ketone, and 2.94 g of acetonitrile, which had been previously argon-substituted, was added to the above reaction solution, and the mixture was reacted at 60° C. for 10 hours. As a result, a prepolymer (Mw: 9180) containing a hydrophilic block A1 and a hydrophobic block B was obtained.

[0130] A mixed solution of 4.16 g of BMA, 2.20 g of MMA, 1.79 g of MAA, 0.08 g of AIBN, 1.84 g of methyl ethyl ketone, and 11.66 g of acetonitrile, which had been previously purged with argon, was added to the above reaction solution, and the mixture was reacted at 60° C. for 24 hours. As a result, a polymer (Mw: 13,300) containing hydrophilic block A1, hydrophobic block B, and hydrophilic block A2 was obtained.

[0131] After the reaction was completed, 108 g of methyl ethyl ketone was added to the reaction solution, which was then poured into 0.63 L of heptane under stirring. The precipitated polymer was filtered by suction and dried to obtain a block copolymer P-2.

[0132] <Preparation of Block Copolymer P-3> Block copolymer P-3 was prepared in the same manner as block copolymer P-1, except that the monomer composition of hydrophilic block A2 was changed as shown in Table 1.

[0133] <Preparation of Block Copolymer P-4> Into a flask equipped with an argon gas inlet tube and a stirring blade were placed 1165.0 g of BzMA, 116.5 g of MAA, 116.5 g of BTEE, 43.0 g of DBDT, 6.4 g of AIBN, and 1282.0 g of methyl ethyl ketone, and the mixture was reacted at 60° C. for 24 hours.

[0134] To the above reaction solution, a mixed solution of 1388.0 g of BMA, 734.0 g of MMA, 596.0 g of MAA, 12.8 g of AIBN, 538.0 g of methyl ethyl ketone, 1677.0 g of acetonitrile, and 503.0 g of methanol, which had been previously purged with argon, was added, and the reaction was carried out at 60° C. for 28 hours.

[0135] After the reaction was completed, 18.7 kg of methyl ethyl ketone was added to the reaction solution, which was then poured into 107 L of heptane under stirring. The precipitated polymer was filtered by suction and dried to obtain a block copolymer.

[0136] <Preparation of random copolymer P-5> A random copolymer P-5 having the monomer composition shown in Table 1 was prepared by known radical polymerization.

[0137] Table 1 shows the compositions of the block copolymers P-1 to P-4 and the random copolymer P-5. [Table 1]

[0138] In Table 1, the acid value is a value measured according to the measurement method of JIS K0070: 1992. The molecular weight is a weight average molecular weight Mw, and is a value obtained by the GPC method in terms of polystyrene.

[0139] 1-2. Preparation of pigment dispersion <Preparation of Pigment Dispersions A-1 to A-5> 20.0 parts by mass of carbon black pigment was mixed with a block copolymer shown in Table 2 as a pigment dispersant, in which the amount added relative to the pigment was 30% by mass, 20 parts by mass of propylene glycol (PG), 5 parts by mass of 1,2-hexanediol (1,2-HD), and 0.5 parts by mass of TEGO Wet 250, along with ion-exchanged water to obtain an aqueous pigment dispersion with a pigment concentration of 20.0%.

[0140] Dispersion treatment was performed using a horizontal media disperser (Labostar Mini LMZ015, zirconia bead diameter 0.3 mm, manufactured by Ashizawa Finetech Co., Ltd.) to prepare pigment dispersions A-1 to A-5 with a pigment concentration of 20.0%. The volume-based average particle size of the pigment particles was measured using a particle size distribution measuring device (Zeta Nanosizer 1000HS, manufactured by Malvern Instruments).

[0141] Table 2 shows the pigment dispersants used: Pigment Dispersions A-1 to A-5. [Table 2]

[0142] 1-3. Preparation of ink <Preparation of Ink B-1> The following components were mixed to obtain ink B-1. Pigment dispersion A-1: ​​15 parts by weight Urethane resin Takelac W-6110 (Mitsui Chemicals, Tg: -20°C): 10 parts by mass as solid content Glycerin: 10 parts by weight Propylene glycol: 20 parts by weight Proxel GXL(S) (preservative): 0.05 parts by weight Olfin E1010 (manufactured by Nissin Chemical Industry Co., Ltd., surfactant): 0.1 parts by mass Ion exchange water: remaining amount The amount of ion-exchanged water was adjusted so that the total amount of ink was 100 parts by mass.

[0143] <Preparation of Inks B-2 to B-17> Inks B-2 to B-17 were prepared in the same manner as Ink B-1, except that the pigment dispersion, urethane resin, and added amounts were changed as shown in Table 3.

[0144] The composition of the main components of the ink prepared is shown in Table 3. The type of urethane resin used in the ink is shown in Table 4.

[0145] [Table 3] [Table 4]

[0146] 2. Preparation of Treatment Solutions 2-1. Preparation of cationic compounds <Preparation of Compound 1> 38% by mass of PEG600 (Kanto Chemical Co., Ltd., number average molecular weight 600), 1% by mass of trimethylolpropane, 5% by mass of N-methyl-N,N-diethanolamine, 23% by mass of tolylene diisocyanate, and 33% by mass of methyl ethyl ketone were mixed in a reaction vessel, and the reaction was carried out at a reaction temperature of 70 to 75°C to obtain a cationic urethane compound. After 3% by mass of acetic acid was added and mixed to the obtained cationic urethane compound, water was added and mixed uniformly, and then MEK was recovered to obtain an aqueous solution of a water-soluble cationic urethane compound containing 25% by mass of active ingredient.

[0147] <Preparation of Compound 2> An aqueous solution of a water-soluble cationic urethane compound was obtained in the same manner as in Compound 1, except that the amount of PEG600 was changed to 46% by mass and the amount of tolylene diisocyanate was changed to 15% by mass.

[0148] <Preparation of Compound 3> An aqueous solution of a water-soluble cationic urethane compound was obtained in the same manner as in the preparation of Compound 1, except that tolylene diisocyanate was changed to isophorone diisocyanate.

[0149] <Preparation of Compound 4> 38% by mass of polycarbonate polyol (Nippolan 981, manufactured by Nippon Polyurethane Industry Co., Ltd., number average molecular weight 1000), 1% by mass of trimethylolpropane, 5% by mass of N-methyl-N,N-diethanolamine, 33% by mass of isophorone diisocyanate, and 33% by mass of methyl ethyl ketone were mixed in a reaction vessel and reacted at a reaction temperature of 70 to 75°C to obtain a cationic urethane compound. 3% by mass of acetic acid was added to and mixed with the obtained cationic urethane compound, water was then added and mixed uniformly, and the MEK was then recovered to obtain an aqueous solution of water-dispersible cationic urethane compound 4 containing 25% by mass of active ingredient.

[0150] <Preparation of Compound 5> An aqueous solution of a water-dispersible cationic urethane compound containing 25% by mass of active ingredient was obtained in the same manner as Compound 4, except that the 38% by mass of polycarbonate polyol (Nippolan 981, Nippon Polyurethane Industry Co., Ltd., number average molecular weight 1000) was changed to 36% by mass of polycarbonate polyol (Nippolan 981, Nippon Polyurethane Industry Co., Ltd.) and 2% by mass of PEG600.

[0151] <Compounds 6~8> Compound 6: Hydran CP-7010 (manufactured by Dainippon Ink and Chemicals, Inc., water-dispersible resin, solid content 30% by mass) Compound 7: Superflex 650 (Dai-ichi Kogyo Seiyaku Co., Ltd., water-dispersible resin, solid content 25% by mass) Compound 8: Mowinyl 6969D (styrene-acrylic resin, solid content 42% by mass, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.)

[0152] The physical properties of the obtained compounds 1 to 8 are shown in Table 5.

[0153] [Table 5]

[0154] The weight average molecular weights Mw of Compounds 1 to 8 were measured by gel permeation chromatography in terms of polystyrene.

[0155] 2-2. Preparation of processing solution <Preparation of Processing Solutions 1 to 12> Treatment solutions were prepared by mixing the components shown in Table 6. The values ​​in the table represent parts by mass. The pH of each treatment solution at 25°C was measured with a pH meter and was in the range of 3.5 to 4.5.

[0156] [Table 6]

[0157] 3. Image formation and evaluation 3-1. Image formation <Test 1> An image was formed using the ink and treatment liquid prepared above. First, as an image forming apparatus, a simple printing test machine equipped with a KM1024i head manufactured by Konica Minolta, Inc. was prepared. The ink and treatment liquid prepared above were set in the head.

[0158] (1) Pretreatment As the fabric, cotton satin (100% cotton) was prepared. Next, pre-treatment PC-1 was applied to the surface of the fabric at a rate of 10 g / m 2 After applying the ink by the inkjet method so as to obtain an application amount of 100° C., the ink was dried at 100° C. for 2 minutes.

[0159] <Preparation of pretreatment solution PC-1> The following components were mixed to prepare pretreatment solution PC-1. Flocculant 1: Unisense KHE100L (manufactured by Senka Co., Ltd.): 4 parts by mass Glycerin: 10 parts by weight Propylene glycol: 20 parts by weight Proxel GXL(S) (preservative): 0.05 parts by weight Olfin E1010 (manufactured by Nissin Chemical Industry Co., Ltd., surfactant): 0.1 parts by mass Ion-exchanged water: 44.85 parts by weight

[0160] (2) Ink application Next, ink B-1 was ejected from the head onto the fabric to form a solid image of 200 mm x 200 mm. The amount of ink applied was 15 g / m 2 It was decided. The ink was ejected at 540 dpi in the main scan direction and 720 dpi in the sub scan direction. Note that dpi represents the number of ink droplets (dots) per 2.54 cm. The ejection frequency was 22.4 kHz. Next, the fabric to which the ink was applied was dried at 150° C. for 3 minutes in a belt conveying dryer to form an image layer.

[0161] (3) Application of treatment liquid Treatment liquid 1 was discharged from the head onto the image layer formed on the fabric, and applied onto the solid image. The image was then dried at 150°C for 3 minutes in a belt conveying dryer to obtain an image-formed product. The amount of treatment liquid applied was 15 g / m 2 It was decided.

[0162] <Tests 2-29> Image formation was carried out in the same manner as in Test 1, except that the combination of ink and treatment liquid was changed as shown in Table 7.

[0163] 3-2.Evaluation The resulting image-formed product was evaluated for (1) image density, (2) resistance to rubbing, and (3) texture by the following methods.

[0164] (1) Image Density The resulting image formation, L * a * b * L in color space * , a * , b * The above was measured at 10 locations using a spectrophotometer "CM-25d" (Konica Minolta, Inc., measurement light source: D65) and the average value was calculated. And each L * Regarding the value of L in test 21, * The relative value was calculated with the value of 100, and the evaluation was performed based on the following criteria. L * The smaller the relative value, the higher the black density, which indicates good performance. 4:L * The relative value of is less than 85 3:L * The relative value of is 85 or more and less than 95 2:L * The relative value of is 95 or more and less than 100 1:L * The relative value of is 100 or more

[0165] (2) Friction resistance Using a Gakushin type friction fastness tester (product name: AB-301, manufactured by Tester Sangyo Co., Ltd.), a JIS color fastness test cloth (JIS L 0803:2011 compliant No. 3-1) was soaked in pure water under conditions of a load of 200.0 g and a speed of 10.0 cm / s, and the cloth was rubbed back and forth 10.0 times on the image forming surface. Thereafter, the dye transfer density onto a test white cloth was evaluated based on the following evaluation criteria. 4: Slight or almost no dye transfer 3: There is some dye transfer. 2: There is some dye transfer and slight ink peeling. 1: The dye transfer concentration is high.

[0166] (3) Texture The obtained image-formed product was subjected to a sensory evaluation using a touch and was rated according to the following criteria. 5: Soft and difficult to distinguish between the image forming surface and the fabric 4: Soft, but the boundary between the image surface and the fabric is slightly visible 3: It is not stiff and is soft, but you can see the boundary between the printed surface and the fabric. 2: It feels stiff and a little hard 1: It feels very stiff and hard

[0167] Furthermore, (4) ink storage stability and (5) ejection stability of the ink used in the above image formation were evaluated by the following methods.

[0168] (4) Ink storage stability For inks B-1 to B-17, the average particle size was measured using a particle size distribution analyzer (Zetasizer Nano S, manufactured by Malvern Instruments) after storage for two weeks in an environment (constant temperature bath) at a temperature of 60° C. The particle size increase rate was calculated from the obtained average particle size and the average particle size before storage, and evaluated based on the following criteria. 3: The increase in average particle size is less than 10% 2: The increase in average particle size is 10% or more but less than 15%. 1: Increase in average particle size is more than 15%

[0169] (5) Discharge stability The ink storage stability and ejection stability of the inks B-1 to B-17 were evaluated by the following methods. After continuous ejection for 10 minutes under image forming conditions, the ink was checked for missing or bent ink using an ejection inspection machine. The ejection stability was evaluated according to the following criteria. The evaluation environment was set to an environmental temperature and humidity of 20°C and 40% RH, and the head surface temperature was 35°C. 5: No problems even with long periods of continuous use 4: No injection failures 3: Slight bending occurs, but no problems. 2: Missing ink occurs during printing 1: Missing injection occurs or injection cannot be performed normally

[0170] The evaluation results of tests 1 to 29 are shown in Table 7. Furthermore, the evaluation results of the ink storage stability and ejection stability are shown in Table 8.

[0171] [Table 7]

[0172] As shown in Table 7, Tests 1 to 7, 13 to 20, and 26, which used inks containing a specific block copolymer as a pigment dispersant, were superior in image density, friction fastness, and texture to Tests 21 to 25, 27, and 29, which used inks containing a diblock dispersant or random dispersant as a pigment dispersant. Also, Test 17, which used a urethane resin as the ink binder resin, was superior in image density, friction fastness, and texture to Test 28, which used an acrylic resin.

[0173] In particular, Tests 2 and 19, which used a low Tg urethane resin for the ink, were found to be superior in image density, resistance to rubbing, and texture.

[0174] In addition, a comparison between Tests 2 and 26 and a comparison between Tests 21 and 27 shows that by using a specific block copolymer, the amount of binder resin used can be reduced with almost no degradation in image quality compared to when a conventional block copolymer is used. In addition, a comparison between Tests 2 and 18 and 21 and 23 shows that by using a specific block copolymer, the amount of pigment dispersant used can be reduced with almost no degradation in image quality compared to when a conventional block copolymer is used. This is presumably because the specific block polymer used as a pigment dispersant has two hydrophilic parts that interact with the urethane resin in the ink and the cationic compound in the treatment liquid, which increases the interaction between the pigment dispersion and the resin and strengthens the fixation of the pigment to the fabric, making it less likely to cause degradation in quality. [Table 8]

[0175] As shown in Table 8, it can be seen that inks B-1 to B-9 and B-15, which contain a predetermined block copolymer as a pigment dispersant, all have good ink storage stability and ejection stability. [Industrial Applicability]

[0176] According to the present invention, it is possible to provide an ink set for ink-jet textile printing and an image forming method capable of forming an image having good uniformity of image density and good resistance to friction without impairing texture.

Claims

1. The composition includes a pigment, a pigment dispersant, a water-dispersible anionic urethane resin, and an aqueous solvent, the pigment dispersant includes a block copolymer including two hydrophilic blocks A arranged at both ends of a molecule and interacting with the pigment, and a hydrophobic block B arranged between the two hydrophilic blocks A; and A treatment liquid containing a water-soluble cationic urethane compound; Including, Ink set for inkjet textile printing.

2. the hydrophilic block A includes a structural unit derived from a hydrophilic monomer that is a vinyl monomer containing a hydrophilic functional group selected from the group consisting of a hydroxyl group, a carboxyl group, and a sulfonic acid group, the content ratio of the structural unit derived from the hydrophilic monomer in the hydrophilic block A is higher than that in the hydrophobic block B; The ink set for ink-jet textile printing according to claim 1 .

3. the hydrophobic block B comprises a structural unit derived from a hydrophobic monomer selected from the group consisting of vinyl monomers containing an aromatic ring group or an alicyclic hydrocarbon group, the content ratio of the structural unit derived from the hydrophilic monomer in the hydrophobic block B is lower than that in the hydrophilic block A; The ink set for ink-jet textile printing according to claim 2.

4. A method for forming an image on a fabric by using the ink set for ink-jet textile printing according to any one of claims 1 to 3, comprising the steps of: applying the inkjet textile printing ink onto the fabric by an inkjet system; applying a treatment liquid onto the fabric; Including, Image forming method.

Citation Information

Patent Citations

  • Overcoat liquid for inkjet printing, ink set for inkjet printing, and coating method

    JP2017149812A

  • Pigment dispersant and manufacturing method therefor, water-based pigment dispersion, and water-based inkjet ink

    JP2019210389A

  • Ink composition and textile printing method

    WO2015152290A1